High-efficiency low-resistance electrostatic spinning multi-layer filtering material for mask filter element and preparation method of high-efficiency low-resistance electrostatic spinning multi-layer filtering material

The multi-layer composite filter material was prepared through electrospinning technology, combined with ZIF-8 and PAA nanofibers, which solved the problems of high resistance and high cost of traditional air filter materials, achieved high efficiency and low resistance air filtration effect, and provided mask filter element. A feasible large-scale production plan.

CN119261345APending Publication Date: 2025-01-07TIAN JIN GONG YE DA XUE SHAO XING KE QIAO YAN JIU YUAN +1

Patent Information

Application Number
CN202411386983.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Traditional air filter materials have high filtration resistance problems in high flow applications, and a single material is difficult to meet filtration needs in complex environments, especially in maintaining cost-effectiveness and productivity.

Method used

Multi-layer composite filter material was prepared through electrospinning technology, ODA and PMDA were dissolved to form beaded PAA nanofiber membrane, and mixed with ZIF-8, and multi-layer structural material was formed after heat treatment. Combined with ultrasonic bonding technology, the preparation process was simplified and Improve the uniform dispersion and stability of the material.

Benefits of technology

It achieves the dual improvement of high filtration efficiency and low resistance, enhances the ability to capture viruses and bacteria, maintains low resistance characteristics and mechanical properties, reduces production costs, and is suitable for the large-scale production and application of mask filter elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119261345A_ABST
    Figure CN119261345A_ABST
Patent Text Reader

Abstract

The invention discloses a high-efficiency low-resistance electrostatic spinning multi-layer filtering material for a mask filter element and a preparation method of the high-efficiency low-resistance electrostatic spinning multi-layer filtering material. The method comprises the following steps: firstly, dissolving ODA and PMDA raw materials in a solvent to prepare a first PAA solution; then, preparing the solution into a first bead-like PAA nanofiber membrane by utilizing an electrostatic spinning technology; the preparation method comprises the following steps: preparing a first PAA / ZIF-8 nanofiber layer, dissolving a ZIF-8 raw material in the first PAA / ZIF-8 nanofiber layer, mixing the ZIF-8 raw material with ODA and PMDA to form a second PAA / ZIF-8 solution, superposing second PAA / ZIF-8 nanofiber layers on the first PAA / ZIF-8 nanofiber layer above and below the first PAA / ZIF-8 nanofiber layer through an electrostatic spinning technology, and carrying out thermal imidization treatment to successfully prepare the multi-layer filter material with a ZIF-8 modified PI / bead-like PI / ZIF-8 modified PI structure. The preparation process provided by the invention is simplified and efficient, and the prepared bead-like multilayer filtering material not only has the characteristics of excellent filtering efficiency and low resistance, but also shows huge application potential in the field of air purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of air purification and filtering materials, and in particular to a multi-layer composite filtering material with high-efficiency filtering performance and low-resistance characteristics prepared by electrostatic spinning technology and a preparation method thereof. Background Art

[0002] With the rapid development of industrialization and urbanization, air quality issues have become a global focus. Fine particles (PM2.5), viruses, bacteria and other harmful substances in the air pose a serious threat to human health and the ecological environment. In order to meet this challenge, it is particularly important to develop high-efficiency and low-resistance air filtration materials.

[0003] Traditional filter materials, such as meltblown cloth and activated carbon fiber, mainly face the problem of high air flow resistance when making masks, which limits their effectiveness in applications requiring high-flow air purification. Therefore, Chinese Patent No. 202311394990.7 developed a beaded sodium alginate (SA) nanofiber membrane, which was prepared by innovative electrospinning technology to solve the problem of high filtration resistance caused by traditional technology. Through precise proportioning and subsequent processing, high-efficiency and low-resistance filtration performance is achieved. However, a single material may still not be sufficient to meet the filtration needs in complex environments.

[0004] Furthermore, Chinese Patent No. 202011125446.9 prepared an advanced mask filter layer preparation technology that combines MOF materials with polyacrylonitrile (PAN). The patent combines MOFs materials MIL-53 (Fe), cellulose and polyacrylonitrile (PAN) to prepare an advanced mask filter layer with antibacterial, high-efficiency filtration and natural degradation functions. Although the combination of MIL-53 (Fe) brings significant performance improvements, there are also some disadvantages, including increased complexity of the preparation process, rising costs, and technical challenges in ensuring uniform dispersion and stable combination of MOFs and nanofibers. In addition, maintaining cost-effectiveness and production efficiency during large-scale production is also a problem that needs to be solved.

[0005] On this basis, this patent achieves better filtration efficiency and lower airflow resistance through multi-layer structural design, solving the limitations of traditional materials and single electrospun nanofiber membranes in high-flow applications. At the same time, it maintains the high adsorption performance and catalytic properties of MOFs materials, reduces costs and improves production efficiency through optimized preparation processes, and ensures the uniform dispersion and stability of materials, providing a practical solution for the large-scale production and application of mask filter materials. Summary of the invention

[0006] The present invention provides a high-efficiency and low-resistance electrospun multilayer filter material and a preparation method for a mask filter element. The first PAA solution is prepared by dissolving ODA and PMDA to form a beaded PAA nanofiber membrane, which is then mixed with ZIF-8 to form a second PAA / ZIF-8 solution, which is stacked and heat-treated to obtain a multilayer structural material. The material has high filtration efficiency, low resistance and excellent mechanical properties, and the simplified preparation process makes it have wide application potential in the field of air purification.

[0007] To achieve the above object, the present invention is implemented through the following technical solutions:

[0008] A high-efficiency, low-resistance electrospun multilayer filter material for a mask filter element and a preparation method thereof, comprising the following steps:

[0009] (1) Preparation of beaded PAA nanofiber membrane: The first PAA solution is prepared by mixing and dissolving ODA and PMDA raw materials in a solvent, and then the beaded PAA nanofiber membrane is made by electrospinning technology, laying the foundation for the preparation of multi-layer composite filter materials;

[0010] (2) Synthesis of ZIF-8 powder: ZIF-8 was prepared by dissolving zinc nitrate hexahydrate and 2-methylimidazole in suitable solvents, mixing, ultrasonicating for 20 min and standing at room temperature, followed by centrifugation and washing and drying with anhydrous methanol to obtain white powdered ZIF-8.

[0011] (3) Preparation of the second PAA / ZIF-8 nanofiber layer: ZIF-8 powder is dissolved in a solvent to prepare a second solution. Subsequently, ODA is added and dissolved, and then reacts with PMDA powder to form a stable PAA / ZIF-8 precursor solution, which is then allowed to stand for 6 hours before being used for electrospinning, covering the first beaded PAA nanofiber membrane to form a uniform second PAA / ZIF-8 nanofiber;

[0012] (4) Bonding: bonding the prepared ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber composite membrane to prepare a filter material;

[0013] (5) Imidization treatment: The ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber membrane was dried at 60-80 °C for 2 h to remove the solvent and set the membrane, and then subjected to a two-stage thermal imidization treatment in a muffle furnace to finally prepare a multilayer filter material.

[0014] Preferably, in the step (1), the ODA and PMDA raw materials are prepared in a solvent to prepare a first PAA solution with a concentration of 20-24 wt%, a spinning voltage of 18-25 kV, a drum speed of 100-200 r / min, and a spinning receiving distance of 10-20 cm.

[0015] Preferably, the solvent in step (1) is one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC) or dimethyl sulfoxide (DMSO).

[0016] Preferably, in step (2), the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:2-8, the solvent is methanol, and the rotation speed during the stirring reaction is 300-600 rpm.

[0017] Preferably, in step (3), the molar ratio of ODA to PMDA is 1:1-1.02, and PMDA is added to the stirred and uniformly dissolved second solution in 7-8 times, and the amount added decreases with the increase in the number of times, and each time the added dianhydride monomer powder is added after it is completely dissolved, and the interval time is about 10-20 minutes.

[0018] Preferably, in the step (3), by controlling the mass ratio of ZIF-8 to PMDA, a precursor solution ZIF-8 / PAA with a doping amount of 1 wt% to 6 wt% is prepared.

[0019] Preferably, in step (3), the concentration of the second PAA / ZIF-8 solution is 26-30wt%, the spinning voltage is 25-35kV, the drum speed is 100-200r / min, the receiver distance is 10-20cm, the ambient temperature is 20-30°C, and the relative humidity is 20-60%.

[0020] Preferably, in step (4), the bonding method of the ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber composite membrane is ultrasonic bonding.

[0021] Preferably, in the thermal imidization process of step (5), the PAA molecules are first converted into PI by heating at 100-200° C. for 15-30 min, and then further heated at 200-300° C. for 20-40 min to complete the imidization.

[0022] Compared with the prior art, the present invention has the following beneficial technical effects:

[0023] Structural optimization: The sandwich structure design uses a beaded nanofiber layer as the core to reduce filtration resistance. At the same time, nanofiber layers with smaller diameters are used on both sides to effectively capture tiny particles, achieving a double improvement in filtration efficiency and low resistance.

[0024] Modification and enhancement: The introduction of ZIF-8 material not only enhances the capture ability of viruses and bacteria, but also further improves the filtration performance after compounding with PI, while maintaining the low resistance characteristics of the filter material.

[0025] Bonding innovation: Ultrasonic bonding technology is used to minimize damage to the electrospun nanomembrane, ensuring high bonding strength and excellent mechanical properties of the composite membrane, effectively avoiding structural changes and performance degradation caused by thermal damage, while retaining the high air permeability and low resistance characteristics of the nanofiber membrane.

[0026] Improved stability: The combination of electrospinning technology and MOFs materials significantly improves the chemical and thermal stability of the materials, allowing the mask filter to maintain its performance in a changing environment, and can be folded for use, and its performance remains stable after washing.

[0027] Sustainability: Successfully developed a new type of nanofiber material, whose performance is comparable to or even exceeds that of high-priced commercial filtration media on the market, while opening up innovative avenues for applications such as battery separators and biological tissue engineering.

[0028] Cost-effectiveness: The preparation process is simplified and the interface compatibility is good, which reduces the production cost, making the high-efficiency and low-resistance mask filter economical and practical, and has a wider market application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope image of the synthesized ZIF-8.

[0030] Figure 2 This is a scanning electron microscope image of the beaded PI nanofiber membrane.

[0031] Figure 3 This is a scanning electron microscope image of the ZIF-8 / PI nanofiber membrane.

[0032] Figure 4 Schematic diagram of the structure of ZIF-8 modified PI / beaded PI / ZIF-8 modified PI multilayer composite filter material. DETAILED DESCRIPTION

[0033] The present invention is described in detail below in conjunction with the accompanying drawings, but it should be noted that the implementation of the present invention is not limited to the following embodiments.

[0034] Example 1

[0035] A high-efficiency, low-resistance electrospun multilayer filter material for a mask filter element and a preparation method thereof, characterized in that it comprises the following steps:

[0036] (1) Preparation of beaded PAA nanofiber membrane: The first PAA solution is prepared by mixing and dissolving ODA and PMDA raw materials in a solvent, and then the beaded PAA nanofiber membrane is made by electrospinning technology, laying the foundation for the preparation of multi-layer composite filter materials;

[0037] (2) Synthesis of ZIF-8 powder: ZIF-8 was prepared by dissolving zinc nitrate hexahydrate and 2-methylimidazole in suitable solvents, mixing, ultrasonicating for 20 min and standing at room temperature, followed by centrifugation and washing and drying with anhydrous methanol to obtain white powdered ZIF-8.

[0038] (3) Preparation of the second PAA / ZIF-8 nanofiber layer: ZIF-8 powder is dissolved in a solvent to prepare a second solution. Subsequently, ODA is added and dissolved, and then reacts with PMDA powder to form a stable PAA / ZIF-8 precursor solution, which is then allowed to stand for 6 hours before being used for electrospinning, covering the first beaded PAA nanofiber membrane to form a uniform second PAA / ZIF-8 nanofiber;

[0039] (4) Bonding: bonding the prepared ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber composite membrane to prepare a filter material;

[0040] (5) Imidization treatment: The ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber membrane was dried at 60-80 °C for 2 h to remove the solvent and set the membrane, and then subjected to a two-stage thermal imidization treatment in a muffle furnace to finally prepare a multilayer filter material.

[0041] Preferably, in the step (1), the ODA and PMDA raw materials are prepared in a solvent to prepare a first PAA solution with a concentration of 20 wt %, a spinning voltage of 20 kV, a drum speed of 150 r / min, and a spinning receiving distance of 16 cm.

[0042] Preferably, the solvent in step (1) is N,N-dimethylformamide (DMF).

[0043] Preferably, in step (2), the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:6, the solvent is methanol, and the rotation speed during the stirring reaction is 300 rpm.

[0044] Preferably, in the step (3), the molar ratio of ODA to PMDA is 1:1.02, and PMDA is added to the stirred and uniformly dissolved second solution in 7 times, and the amount added decreases with the increase in the number of times, and each time the added dianhydride monomer powder is added after it is completely dissolved, and the interval time is about 15 minutes.

[0045] Preferably, in the step (3), by controlling the mass ratio of ZIF-8 to PMDA, a precursor solution ZIF-8 / PAA with a doping amount of 1 wt % is prepared.

[0046] Preferably, in step (3), the concentration of the second PAA / ZIF-8 solution is 26 wt %, the spinning voltage is 30 kV, the drum speed is 200 r / min, the receiver distance is 16 cm, the ambient temperature is 20-30° C., and the relative humidity is 20-60%.

[0047] Preferably, in step (4), the bonding method of the ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber composite membrane is ultrasonic bonding.

[0048] Preferably, in the thermal imidization process of step (5), the PAA molecules are first converted into PI by heating at 140° C. for 30 min, and then further heated at 220° C. for 20 min to complete the imidization.

[0049] Example 2

[0050] A high-efficiency, low-resistance electrospun multilayer filter material for a mask filter element and a preparation method thereof, characterized in that it comprises the following steps:

[0051] (1) Preparation of beaded PAA nanofiber membrane: The first PAA solution is prepared by mixing and dissolving ODA and PMDA raw materials in a solvent, and then the beaded PAA nanofiber membrane is made by electrospinning technology, laying the foundation for the preparation of multi-layer composite filter materials;

[0052] (2) Synthesis of ZIF-8 powder: ZIF-8 was prepared by dissolving zinc nitrate hexahydrate and 2-methylimidazole in suitable solvents, mixing, ultrasonicating for 20 min and standing at room temperature, followed by centrifugation and washing and drying with anhydrous methanol to obtain white powdered ZIF-8.

[0053] (3) Preparation of the second PAA / ZIF-8 nanofiber layer: ZIF-8 powder is dissolved in a solvent to prepare a second solution. Subsequently, ODA is added and dissolved, and then reacts with PMDA powder to form a stable PAA / ZIF-8 precursor solution, which is then allowed to stand for 6 hours before being used for electrospinning, covering the first beaded PAA nanofiber membrane to form a uniform second PAA / ZIF-8 nanofiber;

[0054] (4) Bonding: bonding the prepared ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber composite membrane to prepare a filter material;

[0055] (5) Imidization treatment: The ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber membrane was dried at 70 °C for 2 h to remove the solvent and set the membrane, and then subjected to a two-stage thermal imidization treatment in a muffle furnace to finally prepare a multilayer filter material.

[0056] Preferably, in the step (1), the ODA and PMDA raw materials are prepared in a solvent to prepare a first PAA solution with a concentration of 22 wt %, a spinning voltage of 25 kV, a drum speed of 150 r / min, and a spinning receiving distance of 16 cm.

[0057] Preferably, the solvent in step (1) is N,N-dimethylacetamide (DMAC).

[0058] Preferably, in step (2), the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:8, the solvent is methanol, and the rotation speed during the stirring reaction is 300 rpm.

[0059] Preferably, in the step (3), the molar ratio of ODA to PMDA is 1:1.02, and PMDA is added to the stirred and uniformly dissolved second solution in 9 times, and the amount added decreases with the increase in the number of times, and each time the added dianhydride monomer powder is added after it is completely dissolved, and the interval time is about 15 minutes.

[0060] Preferably, in the step (3), by controlling the mass ratio of ZIF-8 to PMDA, a precursor solution ZIF-8 / PAA with a doping amount of 2 wt % is prepared.

[0061] Preferably, in step (3), the concentration of the second PAA / ZIF-8 solution is 28 wt %, the spinning voltage is 35 kV, the drum speed is 200 r / min, the receiver distance is 16 cm, the ambient temperature is 20-30° C., and the relative humidity is 20-60%.

[0062] Preferably, in step (4), the bonding method of the ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber composite membrane is ultrasonic bonding.

[0063] Preferably, in the thermal imidization process of step (5), the PAA molecules are first converted into PI by heating at 120° C. for 30 min, and then further heated at 240° C. for 40 min to complete the imidization.

[0064] Example 3

[0065] A high-efficiency, low-resistance electrospun multilayer filter material for a mask filter element and a preparation method thereof, characterized in that it comprises the following steps:

[0066] (1) Preparation of beaded PAA nanofiber membrane: The first PAA solution is prepared by mixing and dissolving ODA and PMDA raw materials in a solvent, and then the beaded PAA nanofiber membrane is made by electrospinning technology, laying the foundation for the preparation of multi-layer composite filter materials;

[0067] (2) Synthesis of ZIF-8 powder: ZIF-8 was prepared by dissolving zinc nitrate hexahydrate and 2-methylimidazole in suitable solvents, mixing, ultrasonicating for 20 min and standing at room temperature, followed by centrifugation and washing and drying with anhydrous methanol to obtain white powdered ZIF-8.

[0068] (3) Preparation of the second PAA / ZIF-8 nanofiber layer: ZIF-8 powder is dissolved in a solvent to prepare a second solution. Subsequently, ODA is added and dissolved, and then reacts with PMDA powder to form a stable PAA / ZIF-8 precursor solution, which is then allowed to stand for 6 hours before being used for electrospinning, covering the first beaded PAA nanofiber membrane to form a uniform second PAA / ZIF-8 nanofiber;

[0069] (4) Bonding: bonding the prepared ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber composite membrane to prepare a filter material;

[0070] (5) Imidization treatment: The ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber membrane was dried at 80 °C for 2 h to remove the solvent and set the membrane, and then subjected to a two-stage thermal imidization treatment in a muffle furnace to finally prepare a multilayer filter material.

[0071] Preferably, in the step (1), the ODA and PMDA raw materials are prepared in a solvent to prepare a first PAA solution with a concentration of 24 wt %, a spinning voltage of 18 kV, a drum speed of 150 r / min, and a spinning receiving distance of 16 cm.

[0072] Preferably, the solvent in step (1) is N,N-dimethylformamide (DMF).

[0073] Preferably, in step (2), the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:6, the solvent is methanol, and the rotation speed during the stirring reaction is 300 rpm.

[0074] Preferably, in step (3), the molar ratio of ODA to PMDA is 1:1.02, and PMDA is added to the stirred and uniformly dissolved second solution in 8 times, and the amount added decreases with the increase in the number of times, and each time the added dianhydride monomer powder is added after it is completely dissolved, and the interval time is about 15 minutes.

[0075] Preferably, in the step (3), by controlling the mass ratio of ZIF-8 to PMDA, a precursor solution ZIF-8 / PAA with a doping amount of 3 wt % is prepared.

[0076] Preferably, in step (3), the concentration of the second PAA / ZIF-8 solution is 26 wt %, the spinning voltage is 30 kV, the drum speed is 200 r / min, the receiver distance is 16 cm, the ambient temperature is 20-30° C., and the relative humidity is 20-60%.

[0077] Preferably, in step (4), the bonding method of the ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber composite membrane is ultrasonic bonding.

[0078] Preferably, in the thermal imidization process of step (5), the PAA molecules are first converted into PI by heating at 160° C. for 20 min, and then further heated at 260° C. for 30 min to complete the imidization.

[0079] Example 4

[0080] A high-efficiency, low-resistance electrospun multilayer filter material for a mask filter element and a preparation method thereof, characterized in that it comprises the following steps:

[0081] (1) Preparation of beaded PAA nanofiber membrane: The first PAA solution is prepared by mixing and dissolving ODA and PMDA raw materials in a solvent, and then the beaded PAA nanofiber membrane is made by electrospinning technology, laying the foundation for the preparation of multi-layer composite filter materials;

[0082] (2) Synthesis of ZIF-8 powder: ZIF-8 was prepared by dissolving zinc nitrate hexahydrate and 2-methylimidazole in suitable solvents, mixing, ultrasonicating for 20 min and standing at room temperature, followed by centrifugation and washing and drying with anhydrous methanol to obtain white powdered ZIF-8.

[0083] (3) Preparation of the second PAA / ZIF-8 nanofiber layer: ZIF-8 powder is dissolved in a solvent to prepare a second solution. Subsequently, ODA is added and dissolved, and then reacts with PMDA powder to form a stable PAA / ZIF-8 precursor solution, which is then allowed to stand for 6 hours before being used for electrospinning, covering the first beaded PAA nanofiber membrane to form a uniform second PAA / ZIF-8 nanofiber;

[0084] (4) Bonding: bonding the prepared ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber composite membrane to prepare a filter material;

[0085] (5) Imidization treatment: The ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber membrane was dried at 80 °C for 2 h to remove the solvent and set the membrane, and then subjected to a two-stage thermal imidization treatment in a muffle furnace to finally prepare a multilayer filter material.

[0086] Preferably, in the step (1), the ODA and PMDA raw materials are prepared in a solvent to prepare a first PAA solution with a concentration of 22 wt %, a spinning voltage of 25 kV, a drum speed of 150 r / min, and a spinning receiving distance of 16 cm.

[0087] Preferably, the solvent in step (1) is N,N-dimethylacetamide (DMAC).

[0088] Preferably, in step (2), the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:8, the solvent is methanol, and the rotation speed during the stirring reaction is 400 rpm.

[0089] Preferably, in the step (3), the molar ratio of ODA to PMDA is 1:1.02, and PMDA is added to the stirred and uniformly dissolved second solution in 7 times, and the amount added decreases with the increase in the number of times, and each time the added dianhydride monomer powder is added after it is completely dissolved, and the interval time is about 20 minutes.

[0090] Preferably, in the step (3), by controlling the mass ratio of ZIF-8 to PMDA, a precursor solution ZIF-8 / PAA with doping amounts of 1 wt% and 3 wt% respectively is prepared.

[0091] Preferably, in step (3), the concentration of the second PAA / ZIF-8 solution is 26 wt %, the spinning voltage is 35 kV, the drum speed is 200 r / min, the receiver distance is 16 cm, the ambient temperature is 20-30° C., and the relative humidity is 20-60%.

[0092] Preferably, in step (4), the bonding method of the ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber composite membrane is ultrasonic bonding.

[0093] Preferably, in the thermal imidization process of step (5), the PAA molecules are first converted into PI by heating at 100° C. for 20 min, and then further heated at 200° C. for 30 min to complete the imidization.

[0094] The filter material prepared by the above method was made into 4 samples, and the test data of their filtration efficiency and filtration resistance are shown in Table 1.

[0095] Table 1

[0096]

[0097] It can be seen from the above results that by adjusting the concentration of the solution, the present invention can easily prepare a beaded PI nanofiber membrane that is both efficient and low-resistance. The doping of ZIF-8 further enhances the material's ability to intercept particulate matter in the air, achieves high filtration efficiency, and greatly reduces the resistance to air flow. This multi-layer nanofiber membrane has a stable structure, high filtration accuracy, excellent air permeability, and low filtration resistance. In the filtration test, the filtration efficiency of PM2.5 reached 99.9%, and the pressure drop was only 33Pa, meeting the strict requirements of modern air purification technology for high-performance filtration materials.

[0098] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the present invention. The present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made within the essential scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A high-efficiency, low-resistance electrospun multilayer filter material for mask filter element and a preparation method thereof, characterized in that: The following steps are involved: (1) Preparation of beaded PAA nanofiber membrane: The first PAA solution is prepared by mixing and dissolving ODA and PMDA raw materials in a solvent, and then the beaded PAA nanofiber membrane is made by electrospinning technology, laying the foundation for the preparation of multi-layer composite filter materials; (2) Synthesis of ZIF-8 powder: ZIF-8 was prepared by dissolving zinc nitrate hexahydrate and 2-methylimidazole in suitable solvents, mixing, ultrasonicating for 20 min and standing at room temperature, followed by centrifugation and washing and drying with anhydrous methanol to obtain white powdered ZIF-8. (3) Preparation of the second PAA / ZIF-8 nanofiber layer: ZIF-8 powder is dissolved in a solvent to prepare a second solution. Subsequently, ODA is added and dissolved, and then reacts with PMDA powder to form a stable PAA / ZIF-8 precursor solution, which is then allowed to stand for 6 hours before being used for electrospinning, covering the first beaded PAA nanofiber membrane to form a uniform second PAA / ZIF-8 nanofiber; (4) Bonding: bonding the prepared ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber composite membrane to prepare a filter material; (5) Imidization treatment: The ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber membrane was dried at 60-80 °C for 2 h to remove the solvent and set the membrane, and then subjected to a two-stage thermal imidization treatment in a muffle furnace to finally prepare a multilayer filter material.

2. A high-efficiency, low-resistance electrospun multilayer filter material for a mask filter element and a preparation method thereof according to claim 1, characterized in that: In the step (1), ODA and PMDA raw materials are prepared in a solvent to prepare a first PAA solution with a concentration of 20-24 wt%, a spinning voltage of 18-25 kV, a drum speed of 100-200 r / min, and a spinning receiving distance of 10-20 cm.

3. A high-efficiency, low-resistance electrospun multilayer filter material for a mask filter element and a preparation method thereof according to claim 1, characterized in that: In the step (2), the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:2-8, the solvent is methanol, and the rotation speed during the stirring reaction is 300-600 rpm.

4. A high-efficiency, low-resistance electrospun multilayer filter material for a mask filter element and a preparation method thereof according to claim 1, characterized in that: In the step (3), the molar ratio of ODA to PMDA is 1:1-1.

02. PMDA is added to the stirred and uniformly dissolved second solution in 7-8 times. The amount added decreases with the increase in the number of times. Each time, the dianhydride monomer powder added needs to be completely dissolved before the next addition. The interval time is about 10-20 minutes.

5. A high-efficiency, low-resistance electrospun multilayer filter material for a mask filter element and a preparation method thereof according to claim 1, characterized in that: In the step (3), the concentration of the second PAA / ZIF-8 solution is 26-30wt%, the spinning voltage is 25-35kV, the drum speed is 100-200r / min, the receiver distance is 10-20cm, the ambient temperature is 20-30°C, and the relative humidity is 20-60%.

6. A high-efficiency, low-resistance electrospun multilayer filter material for a mask filter element and a preparation method thereof according to claim 1, characterized in that: In the step (4), the bonding method of the ZIF-8 modified PI / beaded PI / ZIF-8 modified PI nanofiber composite membrane is ultrasonic bonding.

7. A high-efficiency, low-resistance electrospun multilayer filter material for a mask filter element and a preparation method thereof according to claim 1, characterized in that: In the thermal imidization process of step (5), the PAA molecules are first converted into PI by heating at 100-200° C. for 15-30 min, and then further heated at 200-300° C. for 20-40 min to complete the imidization.

Citation Information

Patent Citations

  • Method for preparing MOF / cellulose / polyacrylonitrile mask filter element layer

    CN112626718A

  • Preparation method of beaded sodium alginate nanofiber membrane

    CN117449035A

  • High-efficiency and low-resistance nanofiber air filtering material for gauze mask and preparation method of filtering material

    CN104645715A

  • Method for manufacturing electrospun nanofiber gas filtering material in mass manner

    CN105133187A

  • Electrospun polyimide nano fiber high-temperature filter material

    CN108837598A

Cited By

  • PA6 / PEO (Polyamide 6 / Polyethylene Oxide) micro-nanofiber air filtering membrane with bent form and preparation method thereof

    CN119909549A

  • PA6 / PEO micro / nanofiber air filter membrane with curved shape and its preparation method

    CN119909549B